The role of food and land use systems in achieving India's sustainability targets. (1st July 2022) - Jha, Chandan Kumar; Singh, Vartika; Stevanović, Miodrag; Dietrich, Jan Philipp; Mosnier, Aline; Weindl, Isabelle; Popp, Alexander; Traub, Guido Schmidt; Ghosh, Ranjan Kumar; Lotze-Campen, Hermann
Abstract: The food and land use sector is a major contributor to India's total greenhouse gas (GHG) emissions. On one hand, India is committed to sustainability targets in the Agriculture, Forestry and Other Land Use (AFOLU) sectors, on the other, there is little clarity whether these objectives can align with national developmental priorities of food security and environmental protection. This study fills the gap by reviewing multiple corridors to sustain the AFOLU systems through an integrated assessment framework using partial equilibrium modeling. We create three pathways that combine the shared socio-economic pathways with alternative assumptions on diets and mitigation strategies. We analyze our results of the pathways on key indicators of land-use change, GHG emissions, food security, water withdrawals in agriculture, agricultural trade and production diversity. Our findings indicate that dietary shift, improved efficiency in livestock production systems, lower fertilizer use, and higher yield through sustainable intensification can reduce GHG emissions from the AFOLU sectors up to 80% by 2050. Dietary shifts could help meet EAT-Lancet recommended minimum calorie requirements alongside meeting mitigation ambitions. Further, water withdrawals in agriculture would reduce by half by 2050 in the presence of environmental flow protection and mitigation strategies. We conclude by pointing towards specific cstrategic policy design changes that would be essential to embark on such a sustainable pathway.